Analysis, reduction and comparison of the life cycle environmental costs of an eco-neighborhood in Belgium. (July 2019) - Nematchoua, Modeste Kameni; Reiter, Sigrid
Highlights: The highest environmental costs of An eco- neighborhood is due to eutrophication (55.4%). The waste is one of components which, has the greatest impact on the overall environment. Vertical density facilitates 1% cumulative increase on cost indicators. Recovery of rainwater facilitates 20.4% cumulative decrease on cost indicators. Abstract: The protection of the environment is one of the main objectives in the European Union. The aim is to protect Nature, that is constantly revolting against the strong mechanization and the new technologies. An environmental cost is the environmental impact of a product, based on its damage and prevention charges. The main purposes of this research are to quantify the different environmental damages generated by a sustainable neighborhood and also, to evaluate those ones in a life cycle of 80 years, as well as the damages derived from influence of water management and urban density on the environment. Twelve environmental impacts were evaluated by the Pleiades and Nova-EQUER simulation software, under four phases (construction, use, renovation and demolition), before being translated into costs to the ecosystem. The results show that the highest harm of a sustainable neighborhood in Belgium, are due to the eutrophication (55.4%), and the greenhouse gas (31.2%) impacts, apart from the natural components, which, their greatest harms on the overall environmental cost balance are: the water (35.3%), the waste (21.9%), and the transport (18.1%). A neighborhood with a good rainwater recovery system allows to save the 76% of the costs related to the water scarcity. The rubbish produces around the 60% of the expense costs, due to the odor impact and around the 43% are related to the health damages.